The Influence of Product Quality, Brand Image and Brand Trust on The Decision to Purchase a Yamaha Mio Motorcycle at the Source Multiera Motor Dealer Pasar Minggu South Jakarta - Sylvi Sakinah; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
The aim of the research is to determine and analyze the influence of product quality, brand image and brand trust on purchasing decisions for Yamaha Mio motorbikes. The data source for this research uses primary data in the form of a questionnaire given to 100 Yamaha Mio Motorbike respondents at the Sumber Multiera Dealer, Pasar Minggu, South Jakarta. The sampling technique in this research used the purposive sampling method. The data analysis technique used was inferential analysis with multiple linear regression and used t-statistics which had been processed in SPSS version 23.0. The results of this research can be seen from the hypothesis test where product quality has a positive influence on purchasing decisions, this is proven by the tcount value of 2.790 with a significant value of 0.006, brand image has a positive influence on purchasing decisions, this is proven by the tcount value of 2.035 with a value significant 0.045, brand trust has a positive influence on purchasing decisions, this is proven by the t value of 2.652 with a significant value of 0.009.